Cation‐Directed Isomerization of the U28 Uranyl‐Peroxide Cluster. Issue 46 (10th October 2017) - Oliveri, Anna F.; Colla, Christopher A.; Callahan, Joseph R.; Bogard, Gwendolyn; Qiu, Jie; Dembowski, Mateusz; Burns, Peter C.; Casey, William H.
Abstract : The conformational dynamics of nanometer‐sized actinide ions are exceptionally sensitive to the choice of counter‐cations. A new means of following these dynamics in solution is presented that follows 1 H NMR signals. The direct bond between hydrogen and phosphorus atoms in the bridging phosphonic groups of the [(UO2 )28 (O2 )20 (PHO3 )24 (H2 O)12 ] 32– (U28 ) cluster allows unparalleled recording of the orientations of these bridges in situ. The µ3 ‐PHO3 bridges are organized into two supersets of conformers (facing inward vs. outward from the cluster), but each of these supersets additionally have four subsets that can be identified based upon orientations of the lone pairs of electrons in the associated oxygen atoms. The ensemble of these subsets changes over days or weeks depending upon bulk solution chemistry, temperature, and pressure. They also reflect cations trapped within the molecule. The 1 H NMR spectra at room temperature indicate that the molecular orientation of this enormous ion tunes itself in response to solution composition, which suggests a strategy for selecting host–guest combinations. Abstract : The phosphonic bridges of a nanometer‐sized anion, [(UO2 )28 (O2 )20 (PHO3 )24 (H2 O)12 ] 32– (U28 ), form an array of conformers that depend sensitively on the identity of counterions. The hydrogen atom of the µ3 ‐PHO3 bridges can face inward or outward from the cluster. Four additional subsets can be distinguished by 1 H NMR spectroscopy, which correspond to the directions of the lone pairs on the oxygen atoms.